2011
DOI: 10.1055/s-0030-1261031
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Electrocatalytic Cyclization of 4,4′-(Arylmethylene)bis(1H-pyrazol­-5-ols) to (5R*,6R*)-11-Aryl-4,10-dimethyl-2,8-diphenyl-2,3,8,9-tetraazadispiro[4.0.4.1]undeca-3,9-diene-1,7-diones

Abstract: Indirect electrochemical oxidation of 4,4¢-(arylmethylene)bis(1H-pyrazol-5-ols) in methanol in an undivided cell in the presence of sodium bromide results in highly efficient formation of the corresponding bis(spiro-2,4-dihydro-3H-pyrazol-3-one)cyclopropanes with 85-96% substance yields and 70-80% current efficiency. NMR and single crystal X-ray diffraction indicate that the products are formed exclusively as (R*,R*)-isomers. The application of this effective indirect electrochemical approach to the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 4 publications
(5 reference statements)
0
18
0
Order By: Relevance
“…18 Taking into consideration the above results and the data for the mechanisms of the electrocatalytic transformation of carbonyl compounds and CH-acids into substituted cyclopropanes [26][27][28] as well as the mechanism of the stereoselective electrocatalytic cyclization of 4,4′-IJarylmethylene)bis-IJ1H-pyrazol-5-ols) (1) into fused bispyrazolone cyclopropanes (2), 18 the following mechanism for the electrocatalytic transformation of aldehydes (3) and two equivalents of pyrazolin-5-one (4) into bispyrazolone cyclopropanes (2) is proposed. Nevertheless, in the NMR spectra of 2a-i, only a single set of signals were identified assuming stereoselective formation of individual diastereoisomers.…”
Section: Resultsmentioning
confidence: 99%
“…18 Taking into consideration the above results and the data for the mechanisms of the electrocatalytic transformation of carbonyl compounds and CH-acids into substituted cyclopropanes [26][27][28] as well as the mechanism of the stereoselective electrocatalytic cyclization of 4,4′-IJarylmethylene)bis-IJ1H-pyrazol-5-ols) (1) into fused bispyrazolone cyclopropanes (2), 18 the following mechanism for the electrocatalytic transformation of aldehydes (3) and two equivalents of pyrazolin-5-one (4) into bispyrazolone cyclopropanes (2) is proposed. Nevertheless, in the NMR spectra of 2a-i, only a single set of signals were identified assuming stereoselective formation of individual diastereoisomers.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Elinson and co‐workers demonstrated that this synthetic strategy could also be used to construct bis(spiro‐2,4‐dihydro‐3 H ‐pyrazol‐3‐one)cyclopropanes 58 from 4,4′‐(arylmethylene)bis(1 H ‐pyrazol‐5‐ols) 57 with NaBr as the mediator (Scheme ) …”
Section: α‐C–x Bond Formation From In Situ Electrogenerated α‐Halogenmentioning
confidence: 99%
“…42 The electrocatalytic cyclotrimerization of dimethyl malonate was carried out in an undivided cell with a Pt anode and a Fe cathode (Scheme 29). 43 Hexamethyl cyclopropanehexacarboxylate (38b) was synthesized in a yield of 70%.…”
Section: Scheme 27mentioning
confidence: 99%
“…Under analogous conditions, cyclotrimerization of ethyl cyanoacetate occurs stereosevectively giving the trans-isomer of triethyl 1,2,3-tricyanocyclopropane-1,2,3-tricarboxylate (42) in 85% yield (Scheme 30). 44 …”
Section: Scheme 29mentioning
confidence: 99%